Koncepcja systemu pomiarowego do diagnozowania dzieci z rozwojowym zaburzeniem koordynacji = Concept of a measurement system for diagnosis of children with a developmental coordination disorder - Eljasz, Dariusz; Miczulski, Wiesław (1949- ); Powroźnik, Piotr; Sobolewski, Łukasz; Szulim, Robert (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents a concept of a measuring system for detecting movement coordination disorders (SP_ZKR) of children. The child`s examination will be conducted during his mini-golf game. Based on the test results obtained from SP_ZKR, the doctor will present the final diagnosis and, if necessary, order appropriate therapy.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne